Analysis of Surgical Recurrence after Larynx Microsurgery for Benign Lesions - Patrial,Maria Theresa Costa Ramos de Oliveira (2021)
Abstract Introduction The study of larynx lesions is of great importance. More than 50% of people with vocal complaints have benign vocal fold alterations and some require surgery. Objective To determine which factors are related to surgical recurrence of benign laryngeal lesions and to determine which videolaryngoscopic diagnoses are related to the risk or protection of surgical relapses over time. Methods Observational, analytical, cross-sectional study with retrospective data collection of 1,383 surgeries in 1,301 patients. Results The mean age at the first surgery was 39.2 years old. The predominant gender was female (65.6%). There were 396 cases of polyps (25.34%), 349 cases of cysts (22.33%), 261 cases of Reinke edema (16.7%), 175 cases of nodules (11.2%), 153 cases of minor structural alterations (MSAs) (9.79%), 94 cases of leukoplakia (6.01%), 77 cases of granulomas (4.93%) and 58 cases of pseudocysts (3.71%). The age presented statistical significance with the risk of surgical relapses (p = 0.016). Male gender was associated with the greatest chance of relapse. Diagnosis of granuloma (p < 0.001) and of leukoplakia (p < 0.001) were associated with a higher risk of surgical recurrence. Cyst diagnosis was associated with protection (p = 0.015) in relation to the chance of further surgeries. Patients with associated lesions, bilaterals or voice professionals did not present a statistically significant association with surgical recurrence. Conclusion Age and gender are statistically related to the increase of surgical relapses. Leukoplakia and granuloma are associated with increased surgical relapses. Patients submitted to cyst microsurgery appear to be protected against surgical recurrence.